Endangering prosperity a global view of the American school - Hanushek, Eric A. (Eric Alan), 1943- (Brookings Institution Press, 2013)
"Compares the performance of American schools with that of other countries against the background of an increasingly globalizing world, introducing new competition for talent, markets, capital, and opportunity, and shows mixed results for U.S. students and recommends areas where American schools and education should be improved"--